A Study of Michigan Farm Bureau's Publication: Rural Living - James Bernstein; Michael V. Doyle; Daniel T. Davis (Journal of Applied Communications, 1986)
The purpose of this study was to evaluate the effectiveness of various communication vehicles of the Michigan Farm Bureau's (MFB) information and public relations division.